the relationship between Competitive orientation and emotional response among footballers - بن التومي بلال (sports creativity, 2025)
n this research, we dealt with the competitive orientation and its relationship to the emotional response of football players, in light of the lack of understanding of psychological phenomena and some behaviors of the players in a way that is reflected on their performance , We decided to delve into this matter , Through which we aim to identify the relationship between competitive orientation and emotional response , In our study, we used the descriptive approach on a sample of 54 players affiliated with the first regional football division championship for the Batna League. The sample was chosen by means of the intentional sampling method , As for the most important results: There is a strong correlation between positive competitive orientation and emotional response - There is a weak correlation between negative competitive orientation and emotional response among football players.